Challenges faced by the HIV testing system in low- and middle-income countries - Rachel S. Kamgaing; Yagai Bouba; Samuel M. Sosso; Jeremiah E. Gabisa; Aubin Nanfack; Joseph Fokam; Laure Ngono; Nadine Fainguem; Michel C.T. Tommo; Krystel N. Zam; Junie F. Yimga; Désiré K. Takou; et al. (AOSIS, 2023)
Introduction: Determining the HIV status of some individuals remains challenging due to multidimensional factors such as flaws in diagnostic systems, technological challenges, and viral diversity. This report pinpoints challenges faced by the HIV testing system in Cameroon. Case presentation: A 53-year-old male received a positive HIV result by a rapid testing algorithm in July 2016. Not convinced of his HIV status, he requested additional tests. In February 2017, he received a positive result using ImmunoComb® II HIV 1 2 BiSpot and Roche cobas electrochemiluminescence assays. A sample sent to France in April 2017 was positive on the Bio-Rad GenScreen™ HIV 1/2, but serotyping was indeterminate, and viral load was 20 copies/mL. The Roche electrochemiluminescence immunoassay and INNO-LIA HIV I/II Score were negative for samples collected in 2018. A sample collected in July 2019 and tested with VIDAS® HIV Duo Ultra enzyme-linked fluorescent assay and Geenius™ HIV 1/2 Confirmatory Assay was positive, but negative with Western blot; CD4 count was 1380 cells/mm3 and HIV proviral DNA tested in France was 'target-not-detected'. Some rapid tests were still positive in 2020 and 2021. Serotyping remained indeterminate, and viral load was 'target-not-detected'. There were no self-reported exposure to HIV risk factors, and his wife was HIV-seronegative. Management and outcome: Given that the patient remained asymptomatic with no evidence of viral replication, no antiretroviral therapy was initiated. Conclusion: This case highlights the struggles faced by some individuals in confirming their HIV status and the need to update existing technologies and develop an algorithm for managing exceptional cases.